Fate and impact of organics in an immersed membrane bioreactor applied to brine denitrification and ion exchange regeneration - McAdam, Ewan J.; Pawlett, Mark; Judd, Simon J. (Elsevier Science B.V., Amsterdam., 2010)
The application of membrane bioreactors (MBRs) to brine denitrification for ion exchange regeneration has been studied. The developed culture was capable of complete brine denitrification at 50 gNaCl.l−1. Denitrification reduced to c.60% and c.70% when salinity was respectively increased to 75 and 100 g.l−1, presumed to be due to reduced growth rate and the low imposed solids retention time (10 days). Polysaccharide secretion was not induced by stressed cells following salt shocking, implying that cell lysis did not occur. Fouling propensity, monitored by critical flux, was steady at 12–15 l.m−2.h−1 during salinity shocking and after brine recirculation, indicating that the system was stable following perturbation. Low molecular weight polysaccharide physically adsorbed onto the nitrate selective anion exchange resin during regeneration reducing exchange capacity by c.6.5% when operating up to complete exhaustion. However, based on a breakthrough threshold of 10 mgNO3−-N.l−1 the exchange capacity was comparative to that determined when using freshly produced brine for regeneration. It was concluded that a denitrification MBR was an appropriate technology for IEX spent brine recov
Keywords: Ion exchange; Brine; Biological denitrification; Salt; Nitrate